2022
DOI: 10.3390/molecules27217248
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Derivatives of Spiropyrrolidine Tethered Indeno-Quinoxaline Heterocyclic Hybrids as Potent Antimicrobial, Antioxidant and Antidiabetic Agents: Design, Synthesis, In Vitro and In Silico Approaches

Abstract: To combat emerging antimicrobial-resistant microbes, there is an urgent need to develop new antimicrobials with better therapeutic profiles. For this, a series of 13 new spiropyrrolidine derivatives were designed, synthesized, characterized and evaluated for their in vitro antimicrobial, antioxidant and antidiabetic potential. Antimicrobial results revealed that the designed compounds displayed good activity against clinical isolated strains, with 5d being the most potent (MIC 3.95 mM against Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Acarbose (ACB) works by slowing the digestion as well as absorption of carbohydrates in the intestine of the host, thereby reducing the postprandial rise in blood glucose levels. The literature has shown that acarbose possesses a notably potential benefit; however, it is reported that ACB is one of the major causes of gastrointestinal disturbance, which limits its level of consumption. , To this effect, the use of compound (1) was evaluated by docking the organic molecule against the 3wyl (α-glucosidase or diabetic receptor) biomolecule. The result obtained is compared with the standard drug (ACB) and reported in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…Acarbose (ACB) works by slowing the digestion as well as absorption of carbohydrates in the intestine of the host, thereby reducing the postprandial rise in blood glucose levels. The literature has shown that acarbose possesses a notably potential benefit; however, it is reported that ACB is one of the major causes of gastrointestinal disturbance, which limits its level of consumption. , To this effect, the use of compound (1) was evaluated by docking the organic molecule against the 3wyl (α-glucosidase or diabetic receptor) biomolecule. The result obtained is compared with the standard drug (ACB) and reported in Table S5.…”
Section: Resultsmentioning
confidence: 99%
“…MD simulation indicated that the ligands remained in the stable docked complex and that the molecules did not leave the VEGFR-2 active site during the 200 ns simulation. Figure 14 shows the molecular structure of the model 25 and the designed derivatives (26)(27)(28)(29)(30) while Table 3 shows the computed activities of these derivatives [101]. Table 3.…”
Section: Quantitative Structure-activity Relationship (Qsar) Modeling...mentioning
confidence: 99%
“…It is a low-melting solid (29-30 • C), soluble in water, and a weak base (pKa = 0.56) [15]. Several studies were performed and displayed a wide range of pharmacological activities for quinoxaline derivatives (Figure 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Additionally, quinoxalines are used for crop protection as a component of insecticides, herbicides, and fungicides [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, isatin derivatives have gained the passion of many researchers owing to their broad spectrum of biological activities. For many years, our research team has focused on the identification of new biologically active biomolecules/small molecules with promising biological activities [ [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ], mainly those α-amylase and α-glucosidase inhibitors [ [71] , [72] , [73] , [74] , [75] , [76] ]. In this context, our work has been devoted to the design and the synthesis of isoxazolidine-isatin hybrids for more potent, selective α-glucosidase and α-amylase inhibitors.…”
Section: Introductionmentioning
confidence: 99%